Professor formador do curso de pedagogia: os saberes que importam para o ensino da matemática nas séries iniciais - Silva, Alessandra Garcia de Andrade e (2008)
This study aimed to investigate the teacher trainer in the Course of Pedagogy, in the area of Mathematics, as regards their knowledge, their training, their working conditions and also to the choices regarding the content it considers necessary for its student, future teacher of the initial series needs to know how teachs mathematics. The person of the search was a teacher trainer who teachs lessons in the area of mathematics, in a course of education in a private university, in Zona Leste of Sao Paulo. The methodology used was the biography, the life story of teacher trainer, built from their course work, made from a semi-structured interview and also comments from the classroom teacher trainer, made on the 2 nd half of 2007. The triangulation between the literature studied, the biography of the trainer and the observations of classes, led to the conclusion that the mathematical content should be addressed with activities that provide research and inquiry, and also make the students to live a little experience how to work in the classroom. It was also concluded that the school is an area of training where the teacher works and is formed at the same time. It was clear, that the quality of the study received during her all life and add to her experience like mathematic teacher in many areas of the Basic Education, has a strong influence in her conviction, and perception of what is necessary for all future teachers to learn and to practice in initial series of Fundamental Learning. Other perception bring us about the study and refers to the importancy of the institutional formed project can have about the quality of formation the students in the course of Pedagogy, this study was showed the care about the formation with the future mathematic s teachers. We can mention the autonomy of the teachers working together and change his experiences each other to improve the formation of the future teacher